Door-to-Door Counseling on Covid-19 Prevention in Selahuni Village, Nagrak Village, Cianjur District - Laila Nur Amalia Danu Miharja; Yogas Bastian Masit; Erwan Setiawan; Nia Jusniani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The emergence of the Covid-19 outbreak has had a huge impact on various social activities. The implementation of health protocols is an absolute thing that must be done by the community in every activity to suppress the spread of the epidemic. However, the facts on the ground are that there are still many people who ignore this. One way to overcome this is by conducting counseling. The extension system used is door-to-door counseling, this strategy is used to prevent crowds and to increase the effectiveness of delivering materials. The program was implemented in Selahuni Village, Nagrak Village, Cianjur District, Cianjur Regency. The purpose of this program is to increase public awareness about the implementation of health protocols, to remind the dangers of Covid-19, and to provide information about the importance of Covid-19 vaccination. The stages of the program are socialization, counseling, distribution of masks, pasting posters, and evaluation. As a result, public awareness about the discipline of health protocols has increased, people have knowledge about the dangers of Covid-19, and people have more awareness to participate in the Covid-19 vaccination program. Hopefully this program can support the government's program to make Indonesia free from Covid-19.